Binomial Coefficients and Powers of One Type of Large Pentadiagonal Matrices (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we derive a general expression for the entries of the $r$thpower $\left( r\in \mathbb{N} \right) $ of one type of the $n× n$ complex pentadiagonal matrix for all $n ≥ 4( r-1)$, in terms of binomial coefficients.
Keywords: Pentadiagonal matrix; Powers of matrices; Binomial coecients; Eigenvalues